Applying a presentation content manifest for signing clinical documents. - Lien C; Hsiao C; Huang L; Kao T (Journal of Digital Imaging, 2010)
In this paper, we demonstrate how to digitally sign a content manifest of a presentable clinical document that contains multiple clinical data with presentations. Only one signature is needed for an entire clinical document with multiple data resources, which can reduce the computation time during signing and verifying processes. In the radiology field, a report may contain text descriptions, images, and annotations that are stored separately in different data resources. The manifest signature would be a proper means for integrity checking for all the clinical data within the manifest. The manifest signature can be extended with a trusted third party to add a digital time signature for long-term verifiability. The performance of the manifest signing compared with that of a traditional digital signing was evaluated. The new manifest signature can be used for signing different types of presentable clinical documents, such HL7 CDA documents and DICOM image reports.